Modest alcohol consumption decreases the risk of non-alcoholic fatty liver disease: a meta-analysis of 43 175 individuals - Sookoian, Silvia Cristina (2014)
Epidemiological studies suggested that the prevalence and the disease severity of non-alcoholic fatty liver disease (NAFLD) are lower for people who drink modest amounts of alcohol than those who are abstainers. Nevertheless, the evidence is still inconclusive because some recently published studies1 showed that modest alcohol consumption (MAC) increases hepatic fat without increasing the risk of advanced fibrosis.